Study of tinctorial behaviour of curaua and banana fibres - Oliveira, Fernando R. (2015)
The ecological benefits of renewable raw materials are clear: they save valuable resources, are environmentally sound and do not cause health problems. Natural fibres have already established a track record in several different areas such as, civil, automobiles, architecture, medicine among others. Numerous investigations are carried out in order to create added value to natural fibre materials such as the stem of the banana tree that are usually discarded in the environment. Curaua, another important natural substrate, is an Amazon-forest plant (Ananas erectifolius) that resembles a pineapple plant. Curaua leaf fibres display a low-production cost and offer a relatively high tensile strength level. Despite these naturals fibres are well established as reinforce in composite materials, the dyeing properties of curaua and banana fibres are not well studied yet.